The Effect of Fermentation Time (as Induced by Fermentation and Must Conditions) on the Chemical Profile and Quality of a Chenin blanc Wine - Van Rooyen, P. C.; Tromp, A (South African Journal of Enology and Viticulture, 2017)
Pattern recognition and simple factorial analyses were applied to chemical profiles determined on wines resulting from an experiment in which the effect of grape solids, assimilable nitrogen, bentonite and fermentation temperature levels as well as culture aeration on total fermentation time was investigated. It was found that fermentation times of the untreated Chenin blanc must could be shortened considerably by increasing grape solid levels and/ or nitrogen as well as temperature. However, it was established that the speeding up of fermentation at sub-optimal assimilable nitrogen levels leads to wines relatively high in higher alcohols and low in esters.